Operation and Maintenance of Secondary Reformer Lessons from Plant experiences (Journal of Chemical Engineering, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/jce.v27i2.17779 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 21-25